Anatomy and Clinical Significance of Sacral Hiatus - Samia Khalid Khokhar; Aisha Qamar (Journal of Bahria University Medical and Dental College, 2021)
The sacral hiatus is a gap on the dorsal surface of the sacrum formed by the non-fusion of the lamina of the fourth and fifth sacral vertebrae. A multitude of anatomical alternations of hiatus have been reported involving metric and non-metric parameters. These have been identified during radiological investigations, surgical procedures or discovered in anatomical and anthropological research studies. For successful outcomes in the clinical setting, it is vital that awareness of identified and newly discovered anatomical variations is achieved through review of literature. Objective of this article is to provide a systematic review of the reported anatomical variations of sacral hiatus with its clinical significance.